ANALISIS KOMODITAS UNGGULAN PERTANIAN UNTUK PENGEMBANGAN EKONOMI DAERAH TERTINGGAL DI KABUPATEN SUMBAWA BARAT - Masniadi, Rudi; Suman, Agus; Sasongko, Sasongko (Journal of Innovation in Business and Economics, 2012)
This research aims to knowing the leading agricultural commodities contained in each area of town left behind in the District West Sumbawa. The instrument analysis used in this study are: Analysis of Location Quotient (LQ) and the Analytical Hierarchy Process (AHP). Results of the analysis of Location Quotient (LQ) indicating that:  the leading agricultural commodities consists of three commodities among other: rice, corn, and cattle (cows).Rresults showed that from the input, the factors inhibiting the development of commodity rice and corn are the scarcity of labor, while breeder lack of the capital to be a factor inhibiting. In the process of production, factors of maintenance and pest control to be a factors inhibiting the development of commodity of rice and corn, while the factor of lack of skills of the breeder to be inhibiting the development of commodity cattle